Electrical control of quantum emitters in a Van der Waals heterostructure - Simon J. U. White; Tieshan Yang; Nikolai Dontschuk; Chi Li; Zai-Quan Xu; Mehran Kianinia; Alastair Stacey; Milos Toth; Igor Aharonovich (Light: Science & Applications, 2022)
The image depicts a schematic illustration of a van der Waals heterostructure used to electrically activate quantum emitters in hexagonal boron nitride.